Advanced Oxidation Protein Products Induce G1/G0-Phase Arrest in Ovarian Granulosa Cells via the ROS-JNK/p38 MAPK-p21 Pathway in Premature Ovarian Insufficiency. (28th July 2021) - Zhou, Xing-Yu; Zhang, Jun; Li, Ying; Chen, Ying-Xue; Wu, Xiao-Min; Li, Xin; Zhang, Xiao-Fei; Ma, Lin-Zi; Yang, Yi-Zhen; Zheng, Ke-Ming; Liu, Yu-Dong; Wang, Zhe; et al.
Abstract : The mechanism underlying the role of oxidative stress and advanced oxidation protein products (AOPPs) in the aetiology of premature ovarian insufficiency (POI) is poorly understood. Here, we investigated the plasma AOPP level in POI patients and the effects of AOPPs on granulosa cells both in vitro and in vivo. KGN cells were treated with different AOPP doses, and cell cycle distribution, intracellular reactive oxygen species (ROS), and protein expression levels were measured. Sprague–Dawley (SD) rats were treated daily with PBS, rat serum albumin, AOPP, or AOPP+ N-acetylcysteine (NAC) for 12 weeks to explore the effect of AOPPs on ovarian function. Plasma AOPP concentrations were significantly higher in both POI and biochemical POI patients than in controls and negatively correlated with anti-Müllerian hormone and the antral follicle count. KGN cells treated with AOPP exhibited G1/G0-phase arrest. AOPP induced G1/G0-phase arrest in KGN cells by activating the ROS-c-Jun N-terminal kinase (JNK)/p38 mitogen-activated protein kinase (MAPK)-p21 pathway. Pretreatment with NAC, SP600125, SB203580, and si-p21 blocked AOPP-induced G1/G0-phase arrest. In SD rats, AOPP treatment increased the proportion of atretic follicles, and NAC attenuated the adverse effects of AOPPs in the ovary. In conclusion, we provide mechanistic evidence that AOPPs may induce cell cycle arrest in granulosa cells via the ROS-JNK/p38 MAPK-p21 pathway and thus may be a novel biomarker of POI.